2021
DOI: 10.3390/app11093931
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Flexural Behavior of Precast Concrete Modular Beam Systems Using Inserted Steel Plates

Abstract: Recently, interest in using precast concrete (PC) modules has increased due to their better seismic performance than steel modules. However, they must be joined by additional elements to ensure structural integration between the modules. The essential aim of the precast concrete module is to ensure structural performance with appropriate connection methods. However, the technical problem of connecting PC modules still needs to be improved. This study proposed a PC modular beam system for improved structural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…These results show good agreement with previous studies, which demonstrated that PC modular members performed at 70-85% of the capacity of general RC monolithic members [38,39]. In addition, the flexural test results were compared to the previous study [20] that proposed the L-shaped PC module and connecting plate. The proposed method of this study had 1.1 times the flexural capacity compared to that of the previous study [20].…”
Section: Load-displacement Relationshipssupporting
confidence: 89%
See 4 more Smart Citations
“…These results show good agreement with previous studies, which demonstrated that PC modular members performed at 70-85% of the capacity of general RC monolithic members [38,39]. In addition, the flexural test results were compared to the previous study [20] that proposed the L-shaped PC module and connecting plate. The proposed method of this study had 1.1 times the flexural capacity compared to that of the previous study [20].…”
Section: Load-displacement Relationshipssupporting
confidence: 89%
“…This study proposed a PC modular beam system using bolted connecting plates to improve the constructability of PC modular beams as shown in Figure 2. In a previous study [20], an L-shaped PC module with bolted connecting plate was proposed considering the role of a shear key in the PC module. However, construction difficulties were observed.…”
Section: Concept Of Modular Concrete Beam With Bolted Connecting Platesmentioning
confidence: 99%
See 3 more Smart Citations